A Contingency‐Based Framework for Managing Enterprise Risk. Issue 3 (March 2015) - Hossein Nezhad Nedaei, Bahareh; Abdul Rasid, Siti Zaleha; Sofian, Saudah; Basiruddin, Rohaida; Amanollah Nejad Kalkhouran, Abolfazl
<x xml:space="preserve">Abstract</x> Although studies focused on contingency theories of enterprise risk management (ERM) as a critical facet of an organization's management control system abound, they have yielded few significant results. A review of the literature on ERM contingency theory and the factors that can affect ERM leads to a discussion of the impact of decentralization, organization size, and enterprise resource planning (ERP). Several hypotheses on possible interactions result in a contingency‐based model for managing enterprise risk that takes into account the effects of these three factors on ERM practices, and offers organizational leaders guidance on how best to improve performance. ©2015 Wiley Periodicals, Inc.